The Current Barriers of Implementation of Green Building Concept in Malaysia - Shee , Cheng Yuan; Omar, Roshartini (Research in Management of Technology and Business, 2023)
The incorporation of green building concepts into the construction sector is gaining traction as a viable solution to meeting public demand for environmentally responsible and sustainable structures. However, the implementation of green building innovations may not be observable due to the obstacles of high capital expenditures, extra work for approval and clearances, and a lack of resources and expertise. The problem to implement the green building in creating sustainable buildings is a lack of knowledge, understanding and high cost. Therefore, the objective of this research is to identify the level of awareness, investigate the current barriers that affect the implementation of green building and strategy to increase the implementation of green building concept in Malaysia. The target respondents for this research is G7 contractors in Kuala Lumpur. This research will use quantitative methods to collect data for this research and it is distributing questionnaires through Google Forms to respondent to get accurate data. The research population is 214 person, sample of respondents is 140 person and respond by 90 person with the respond rate is 64%. As a result of data collection and analysis, the findings in this study revealed the green building concept add more to the construction industry in the future. Furthermore, the level of awareness of the green building concept for G7 contractor was high. However, the main current barrier were mostly high cost to construct. Hence, the government and contractors should play a significant role in increasing the implementation of the green building concept with the effective strategy to bring the green building to the construction industry.